Grid portal technology for web based education of parallel computing courses, applications and researches - Alias, Norma; Islam, Md. Rajibul; Mydin, Suhaimi; Hamzah, Norhafiza; Safiza Abd. Ghaffar, Zarith; Satam, Noriza; Darwis, Roziha (2009)
This paper proposes the web service education technology for postgraduate parallel computing course, e-learning students, real-time solutions and for supervising projects related to the application of parallel computing, that focuses on the fundamental principles to parallel computer architecture, multimedia, communication cost, master-worker model, parallel algorithm, web services and performance evaluations. These courses will actively engage the students in exploring the concepts of the development the parallel algorithm in visualizing the grand challenge applications of mathematical problems. In this paper, the Grid portal technology with open source parallel computing platform is developed and presented that offers the Web Based Education (WBE) dealing with partial differential equation (PDE). The increasing needs of remote and easy-to-access material, growing the aspirations in the development of a web-based service that is easily reached by potential users and easily maintain and update by administrator. The accessible and maintainable characteristics of the web-based service provided are important in providing online solvers service for education in PDE field. C Programming, PVM, MPI and Matlab Distributed Simulation are used to fabricate the system.